Knockout of myomaker results in defective myoblast fusion, reduced muscle growth and increased adipocyte infiltration in zebrafish skeletal muscle. (10th August 2018) - Shi, Jun; Cai, Mengxin; Si, Yufeng; Zhang, Jianshe; Du, Shaojun
Abstract: The fusion of myoblasts into multinucleated muscle fibers is vital to skeletal muscle development, maintenance and regeneration. Genetic mutations in the Myomaker (mymk) gene cause Carey–Fineman–Ziter syndrome (CFZS) in human populations. To study the regulation of mymk gene expression and function, we generated three mymk mutant alleles in zebrafish using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) technology and analyzed the effects of mymk knockout on muscle development and growth. Our studies demonstrated that knockout of mymk resulted in defective myoblast fusion in zebrafish embryos and increased mortality at larval stage around 35–45 days post-fertilization. The viable homozygous mutants were smaller in size and weighed approximately one-third the weight of the wild type (WT) sibling at 3 months old. The homozygous mutants showed craniofacial deformities, resembling the facial defect observed in human populations with CFZS. Histological analysis revealed that skeletal muscles of mymk mutants contained mainly small-size fibers and substantial intramuscular adipocyte infiltration. Single fiber analysis revealed that myofibers in mymk mutant were predominantly single-nucleated fibers. However, myofibers with multiple myonuclei were observed, although the number of nuclei per fiber was much less compared with that in WT fibers. Overexpression of sonic Hedgehog inhibited mymk expression in zebrafish embryos and blocked myoblast fusion. Collectively, these studies demonstrated that mymk is essential for myoblast fusion during muscle development and growth.